AB0205 PREDICTORS OF ULTRASOUND DETECTED INFLAMMATORY FINDINGS IN PATIENTS WITH INFLAMMATORY ARTHRALGIA. (2nd June 2020) - López Gloria, K.; Castrejon, I.; Trives Folguera, L.; Nieto, J. C.; Serrano Benavente, B.; Martínez-Barrio, J.; Rivera, J.; Gonzalez, C.; Monteagudo, I.; Alvaro-Gracia, J. M.; Molina Collada, J.
Abstract : Background: Patients with inflammatory arthralgia (IA) are considered to be at increased risk for progression to RA. US has shown high sensitivity to detect synovitis compared with physical examination. Thus, US is recommended to identify subclinical synovitis in patients without clinical signs of inflammation. Objectives: The objective of our study is to determine the frequency and pattern of US detected inflammatory findings in patients with IA and investigate factors contributing to predict these findings. Methods: An US clinic is scheduled in an academic center running three days every week. A retrospective analysis of our US unit cohort during a period of 6 months was undertaken. Patients with IA and no previous diagnosis of inflammatory arthropathies were included for analysis. Inclusion criteria of IA definition included: severe symptoms presenting in the morning, duration of morning stiffness ≥60 min, symptoms predominantly located in MCP joints and abscense of clinically detected synovitis by the referral rheumatologist. The following routinely collected variables were included in the analysis: demographics, clinical features and laboratory tests. Patients underwent bilateral US examination in GS and PD mode of hands and/or feet according to the European League Against Rheumatism (EULAR) guidelines. The presence of synovitis, tenosynovitis and enthesitis was assessed on a semi quantitative scale (0–3) for Grey Scale(GS)/Power Doppler(PD) or using enthesitis OMERACT definition, respectively. Patients were stratified in two groups based on the presence of US inflammatory findings (synovitis, tenosynovitis or enthesitis with PD signal). First, differences between groups were tested using chi-squared and Student-t tests in the univariate analysis. Second, multivariate logistic regression models were employed to investigate the association between possible predictive factors of US detected inflammatory findings. Results: A total of 57 patients were included in the analysis. Mean age was 55.8±15.2 years, 41 (71.9%) were females, and mean symptoms duration was 11.4±10.4 months (Table 1). A total of 42 (73.7%) patients presented with a polyarticular arthralgia pattern. US inflammatory findings were present in 20 (35.1%) patients (26.3% PD synovitis, 21.1% PD tenosynovitis and 3.5% PD enthesitis). Hands were most commonly involved with PD synovitis at wrists in 19.3% and at MCP in 12.3% of patients (Table 2). For PD tenosynovitis, the flexor MCP 2-5 (5.3%) and compartment IV tenosynovitis (1.8 %) were the most frequent affected locations. Only two patients had PD enthesitis at feet and 6 (10.5%) had erosions in hands or feet at baseline examination. In the univariate analysis, the higher ESR values and the shorter time from symptoms onset were significantly associated with US detected inflammatory findings (p=0.044 and 0.049, respectively). In the multivariate analysis, only ESR values (OR=1, 04; 95%CI 1, 002-1, 078), remained significantly associated with the presence of US inflammatory findings (Table 3 ). Conclusion: PD US inflammatory findings are found in 1 over 3 patients with IA being PD synovitis the most common finding, specially at the wrists and MCP joints. Higher ESR values were significantly associated with the presence of US inflammatory findings. Our data highlights how the use of PD US may be useful to detect subclinical synovitis in patients with IA. Disclosure of Interests: Katerine López Gloria: None declared, Isabel Castrejon: None declared, Laura Trives Folguera Speakers bureau: ROCHE, Juan Carlos Nieto Speakers bureau: Pfizer, Abbvie, MSD, Novartis, Janssen, Lilly, Nordic Pharma, BMS, Gebro, FAES Farma, Roche, Sanofi, Belén Serrano Benavente: None declared, Julia Martínez-Barrio Consultant of: UCB Pharma, Javier Rivera: None declared, Carlos Gonzalez Consultant of: Gilead, Janssen, Novartis, , Speakers bureau: Abbvie, Celgene, Gilead, Janssen, Novartis, Pfizer, Roche, Indalecio Monteagudo: None declared, Jose-Maria Alvaro-Gracia Grant/research support from: Abbvie, Elli-Lilly, MSD, Novartis, Pfizer, Consultant of: Abbvie, BMS, Janssen-Cilag, Elli-Lilly, MSD, Novartis, Pfizer, Sanofi, Tigenix, Roche, UCB, Paid instructor for: Elli-Lilly, Pfizer, Roche, Speakers bureau: Abbvie, BMS, Janssen-Cilag, Elli-Lilly, Gedeon Richter, MSD, Novartis, Pfizer, Sanofi, Tigenix, Roche, UCB, Juan Molina Collada: None declared